Mechanism of tobacco mosaic virus assembly: Incorporation of 4S and 20S protein at pH 7.0 and 20°C - Shire, Steven J. (1981)
The mechanism of assembly of tobacco mosaic virus (TMV) has been investigated at pH 7.0 and 20°C by analytical ultracentrifugation. Under these conditions the overall rates of interconversion of 4S and 20S TMV coat protein are sufficiently slow to make possible measurements of the concentrations of remaining 4S and 20S TMV coat protein after addition of homologous RNA to solutions containing, initially, various mass ratios of 20S protein to 4S protein. It has been possible to measure, by schlieren boundary analysis, the relative rates of incorporation of 4S and 20S TMV protein into the growing nucleoprotein rod over the range of initial 20S:4S protein mass ratios from 93:7 to 18:82. The results show that the amount of incorporation of 20S TMV protein depends on the initial 20S:4S mass ratio between ≈100% and 60% 20S protein but that reconstitution can proceed with ≈100% 20S TMV protein to form full virus-size rods. However, when the initial protein solutions have less than 60% 20S protein, ≈80% of the reconstituted nucleoprotein is preferentially formed from 4S coat protein. The remaining ≈20% appears to require preformed 20S coat protein. These results suggest that a larger region of RNA than previously estimated is involved in the rate-limiting nucleation step in assembly and may explain previously conflicting results concerning the elongation phase of assembly when starting with partially assembled rods.